A RETROSPECTIVE STUDY OF MANAGEMENT OF UNSTABLE INTERTROCHANTERIC FEMORAL FRACTURES IN THE ELDERLY: A COMPARISON OF PROXIMAL FEMORAL NAIL ANTI-ROTATION AND CEMENTED HEMIARTHROPLASTY. - Prakash, Dev; Manav, Ajoy Kumar (Student's Journal of Health Research Africa, 2024)
Background Unstable intertrochanteric femoral fractures (IFF) are common in elderly populations and are correlated with significant morbidity and mortality. Surgical management is the mainstay of treatment, with two commonly used options: Proximal Femoral Nail Antirotation (PFNA) and cemented hemiarthroplasty. This study compared the clinical outcomes, perioperative characteristics, and complication rates in elderly patients with unstable intertrochanteric femoral fractures treated with PFNA versus cemented hemiarthroplasty. Methods A retrospective study involved 78 individuals aged 65 years or older with AO type 31 A2 or A3 unstable IFF. Patients were treated with either PFNA (n=42) or cemented hemiarthroplasty (n=36). The primary outcome was functional recovery assessed by the Harris Hip Score (HHS), while secondary outcomes encompassed operating time, blood loss, hospital stay, and complication rates. SPSS was used for the statistical analysis, with a significance level of p < 0.05. Results With 52 female patients and 26 male patients, the average age was 72.6 ± 4.8 years. Patients in the hemiarthroplasty group showed better functional results, as evidenced by a greater mean HHS (88.6 vs. 85.8, p<0.01). The PFNA group saw decreased intraoperative blood loss (220 mL vs. 410 mL, p<0.001) and a shorter mean operating time (85.3 vs. 110.6 minutes, p<0.001). Patients who underwent hemiarthroplasty, however, spent much less time in the hospital (7.3 vs. 10.2 days, p=0.02). There were no appreciable differences in the rat Conclusion Hemiarthroplasty provided better short-term functional outcomes and a quicker recovery, while PFNA resulted in shorter surgical times and less blood loss. Both methods are effective, but the choice should be individualized based on patient health, fracture type, and rehabilitation needs. Recommendations Further long-term studies are recommended to assess the durability of both treatments. Individual patient factors, such as comorbidities and pre-fracture mobility, should guide treatment decisions to optimize outcomes.